Queens of mystery. Series 2 [videorecording (DVD)] - Graham, Julie, 1965-; Redmond, Siobhan, 1959-; Woodward, Sarah; Hall, Florence; Stevenson, Juliet (Acorn, 2022)
In the picturesque English region of Wildemarsh, Detective Matilda Stone investigates crimes with the aid or, often, meddling of her three mystery-writing aunts, who raised her from childhood. Together, they look into a murder at a health spa, a killing in the contemporary art world, and the theft of an Edgar Allen Poe manuscript. Matilda has decidedly less success with her personal affairs, continuing to pine for Dr. Daniel Lynch even as she begins a new romance. But while Matildas love life hits a snag, she makes headway in the case of her mothers long-ago disappearance despite her aunts best efforts to conceal the secret she most wants to know.